Polymorphonuclear Cell Chemotaxis and Suicidal NETosis: Simultaneous Observation Using fMLP, PMA, H7, and Live Cell Imaging - Delou Pai; Michael Gruber; Sophie-Marie Pfaehler; Andre Bredthauer; Karla Lehle; Benedikt Trabold (Journal of Immunology Research)
Chemotaxis and the formation of suicidal neutrophil extracellular traps (suicidal NETosis) are key functions of polymorphonuclear cells (PMNs). Neutrophil extracellular traps in particular are known to be significantly involved in the severity of inflammatory and immunological disorders such as rheumatoid arthritis and Crohn’s disease. Therefore, detailed knowledge of PMNs is essential for analyzing the mechanisms involved in, and developing new therapies for, such diseases. To date, no standard method to analyze these cell activities has been established. This study used in vitro live cell imaging to simultaneously observe and analyze PMN functions. To demonstrate this, the effects of phorbol-12-myristat-13-acetat (PMA, 0.1-10 nM), N-formylmethionine-leucyl-phenylalanine (fMLP, 10 nM), and protein kinase C inhibitor 1-(5-isoquinolinesulfonyl)-2-methylpiperazine (H7) on PMN chemotaxis and suicidal NETosis were studied. PMA (1 nM-10 nM) resulted in significant concentration-dependent behavior in chemotaxis and an earlier onset of maximum oxidative burst and NET formation of up to 44%. When adding H7, PMA-triggered PMN functions were reduced, demonstrating that all three functions rely mostly on protein kinase C (PKC) activity, while PKC is not essential for fMLP-induced PMN activity. Thus, the method here described can be used to objectively quantify PMN functions and, especially through the regulation of the PKC pathway, could be useful in further clinical studies of immunological disorders.